GOLGI APPARATUS, GERL, AND LYSOSOMES OF NEURONS IN RAT DORSAL ROOT GANGLIA, STUDIED BY THICK SECTION AND THIN SECTION CYTOCHEMISTRY - Novikoff, Phyllis M. (The Rockefeller University Press, 1971)
New insights into the ultrastructure and phosphatase localizations of Golgi apparatus and GERL, and into the probable origin of lysosomes in the neurons of fetal dorsal root ganglia and the small neurons of adult ganglia have come from studying thick (0.5–1.0 µ) as well as thin (up to 500 A) sections by conventional electron microscopy. Tilting the thick specimens, by a goniometer stage, has helped to increase our understanding of the three-dimensional aspects of the Golgi apparatus and GERL. One Golgi element, situated at the inner aspect of the Golgi stack, displays thiamine pyrophosphatase and nucleoside diphosphatase activities. This element exhibits regular geometric arrays (hexagons) of interconnected tubules without evidence of a flattened portion (saccule or cisterna). In contrast, GERL shows acid phosphatase activity and possesses small cisternal portions and anastomosing tubules. Lysosomes appear to bud from GERL. Osmium deposits, following prolonged osmication, are found in the outer Golgi element. Serial 0.5-µ and thin sections of thiamine pyrophosphatase-incubated material demonstrate that, in the neurons studied, the Golgi apparatus is a continuous network coursing through the cytoplasm. Serial thick sections of acid phosphatase-incubated tissue suggest that GERL is also a continuous structure throughout the cytoplasm. Tubules of smooth endoplasmic reticulum, possibly part of GERL, extend into the polygonal compartments of the inner Golgi element. The possible physiological significance of a polygonal arrangement of a phosphatase-rich Golgi element in proximity to smooth ER is considered. A tentative diagram of the Golgi stack and associated endoplasmic reticulum in these neurons has been drawn.